2011
DOI: 10.1007/s11084-011-9246-1
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Adenine and Thymine on Zeolites: FT-IR and EPR Spectroscopy and X-Ray Diffractometry and SEM Studies

Abstract: The interactions of adenine and thymine with and adsorption on zeolites were studied using different techniques. There were two main findings. First, as shown by X-ray diffractometry, thymine increased the decomposition of the zeolites (Y, ZSM-5) while adenine prevented it. Second, zeolite Y adsorbed almost the same amount of adenine and thymine, thus both nucleic acid bases could be protected from hydrolysis and UV radiation and could be available for molecular evolution. The X-ray diffractometry and SEM show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…Previous experimental studies have focused on a variety of mineral surfaces such as alumina, calcite, goethite, mica, olivine, pyrite, rutile, silica, or zinc oxide (Lorenz and Wackernagel, 1987;Holm et al, 1993;Bezanilla et al, 1995;Cohn et al, 2001;Balint et al, 2007;Arora, 2007;Cleaves et al, 2010;Cleaves et al, 2011;Baú et al, 2012;Livi et al, 2013;Zhang et al, 2014;Saha and Sarkar, 2014;Feuillie et al, 2015). Phyllosilicates are assumed to be among the best candidates for the adsorption of nucleotides, a gram of clay can produce up to several hundreds of square meters of reactive surface in water.…”
Section: Introductionmentioning
confidence: 99%
“…Previous experimental studies have focused on a variety of mineral surfaces such as alumina, calcite, goethite, mica, olivine, pyrite, rutile, silica, or zinc oxide (Lorenz and Wackernagel, 1987;Holm et al, 1993;Bezanilla et al, 1995;Cohn et al, 2001;Balint et al, 2007;Arora, 2007;Cleaves et al, 2010;Cleaves et al, 2011;Baú et al, 2012;Livi et al, 2013;Zhang et al, 2014;Saha and Sarkar, 2014;Feuillie et al, 2015). Phyllosilicates are assumed to be among the best candidates for the adsorption of nucleotides, a gram of clay can produce up to several hundreds of square meters of reactive surface in water.…”
Section: Introductionmentioning
confidence: 99%
“…The authors attributed this difference to the difference between the mineral crystal structures and the relative proportions of uncharged surface sites [55]. Compared with the seawater used by Baú et al [25], Benetoli et al [50], and Carneiro et al [52], which is rich in Na + and Cl -, the seawater used in this paper better resembles the oceans of the prebiotic Earth, with high concentrations of Mg 2+ , Ca 2+ , and SO 4…”
Section: Adsorptionmentioning
confidence: 77%
“…The NH 2 group could be also involved in the interaction of adenine with clays, zeolites, and metals [25,50,52,61,62]. However, McNutt et al [63] suggested that the interaction between adenine and Cu (110) occurred through the N atoms from the pyrimidine ring.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Uracil is a demethylated form (a methyl group (CH 3 ) is removed) of thymine. The adsorption of thymine on various minerals and metals such as Pd, Cu, Si, Au, Ag, Cd, clay, graphite, zeolites and rutile TiO 2 has been investigated in the literature. Moreover, the interactions between uracil and various minerals and metals including Cu, Si, Au, Ag, graphite and clays have been addressed.…”
Section: Introductionmentioning
confidence: 99%